Abnormal Brain Functional Network Dynamics in Acute CO Poisoning - Zheng, Hongyi; Liu, Hongkun; Zhang, Gengbiao; Zhuang, Jiayan; Li, Weijia; Zheng, Wenbin (Frontiers in Neuroscience, 2021)
Abstract Aims: Carbon monoxide poisoning is a common condition that can cause severe neurological sequelae. Previous studies have revealed that functional connectivity in carbon monoxide poisoning is abnormal under the assumption that it is resting during scanning and have focused on studying delayed encephalopathy in carbon monoxide poisoning. However, studies of functional connectivity dynamics in the acute phase of carbon monoxide poisoning may provide a more insightful perspective for understanding the neural mechanisms underlying carbon monoxide poisoning. To our knowledge, this is the first study that explores abnormal brain network dynamics in the acute phase of carbon monoxide poisoning. Methods: Combining the sliding window method and k-means algorithm, we identified four recurrent dynamic functional cognitive impairment states from resting-state functional magnetic resonance imaging data from 29 patients in the acute phase of carbon monoxide poisoning and 29 healthy controls. We calculated between-group differences in the temporal properties and intensity of dynamic functional network connectivity (dFNC) states, and we also performed subgroup analyses to separately explore the brain network dynamics characteristics of adult versus child carbon monoxide poisoning groups. Finally, these differences were correlated with patients' cognitive performance in the acute phase of carbon monoxide poisoning and coma duration. Results: We identified four morphological patterns of brain functional network connectivity. During the acute phase of carbon monoxide poisoning, patients spent more time in State 2, which is characterized by positive correlation between sensorimotor network (SMN) and cognitive executive network (CEN), and negative correlation between default mode network (DMN) and SMN.. In addition, the fractional window and mean dwell time of State 2 was positively correlated with coma duration. The subgroup analysis results demonstrated that acute phase of childhood carbon monoxide poisoning had greater dFNC time variability than adult carbon monoxide poisoning. Conclusion: Our findings reveal that patients in the acute phase of carbon monoxide poisoning exhibit dynamic functional abnormalities. Furthermore, children have greater dFNC instability following carbon monoxide poisoning than adults. This advances our understanding of the pathophysiological mechanisms underlying acute carbon monoxide poisoning.